The fiscal and monetary response to COVID‐19: What the Great Depression has – and hasn't – taught us - Selgin, George (Economic Affairs, 2021)
Although some regard the New Deal of the 1930s as exemplifying an aggressive fiscal and monetary response to a severe economic crisis, the US fiscal and monetary policy responses to the COVID‐19 crisis have actually been far more substantial – and, so far, much more effective in reviving aggregate spending. Although many fear that these responses, and the large‐scale increase in bank reserves especially, must eventually cause unwanted inflation, the concurrent sharp decline in money's velocity has thus far more than offset any inflationary effects of money growth, while forward bond prices reflect a general belief that inflation will remain below 2 per cent for at least another decade. Notwithstanding the growth of the Fed's balance sheet, Fed authorities can always check inflation by sufficiently raising the interest return on bank reserves. Nonetheless, recent developments have heightened the risk of ‘fiscal dominance’ of monetary policy at some point in the future.